A review of the efficacy of appetite stimulating medications in hospitalized adults. (25th January 2022) - Steiner, Lea; Brunetti, Luigi; Roberts, Susan; Ziegler, Jane
Abstract: Background: The majority of evidence on efficacy of appetite‐stimulating medications is limited to specific populations and the outpatient treatment setting. However, hospitalized adults remain at risk for poor appetite and inadequate intake. Method: The purpose of this review was to assess recent evidence on the efficacy of dronabinol, megestrol acetate, and mirtazapine (used to stimulate appetite) on promoting change in intake; somatic symptoms, such as appetite and nausea; and weight change during hospital stay. The population was limited to hospitalized adults or adults who demonstrated a need for appetite stimulation during hospitalization. Results: Of the 382 articles screened, four met inclusion criteria (one randomized control trial, two retrospective cohort studies, and one retrospective case series). Based on the studies included, these appetite stimulants have limited efficacy on improving appetite and meal intake. There was no significant change in weight. Conclusion: Current data lack standardization, generalizability, and comparability, and higher quality evidence is needed before conclusions can be identified on the efficacy of dronabinol, megestrol acetate, and mirtazapine in the inpatient setting.